Równanie 1:
[tex]2(x-5)+x = 5x\\3x - 10 = 5x \; \; \; \; /+10\\3x = 5x+10 \; \; \; \; /-5x\\-2x = 10\; \; \; \; /:(-2)\\x = -5[/tex]
Równanie 2:
[tex]x(3x-2)+1 = 2-3x(1-x)\\3x^2 - 2x+1 = 3x^2-3x+2 \; \; \; \; \;/-3x^2\\-2x+1 = -3x+2 \; \; \; \; \;/+3x\\x+1 = 2 \; \; \; \; \;/-1\\x = 1[/tex]
Równanie 3:
[tex]-9\left(2+y\right)-3y+8\ =-2\left(4y+5\right)\\-18+(-9y)+(-3y)+8 = -8y+(-10)\\-12y - 10 = -8y-10 \; \; \; \; \; \; /+8y\\-4y-10 = -10 \; \; \; \; \; \;/+10\\-4y = 0 \; \; \; \; \; \;/:(-4)\\y = 0[/tex]